Francis teaches the piano. He charges each student an enrollment fee of $100 plus $15 per hour of piano lessons. The average cost of lessons for a
student per hour is $25
If h represents the number of hours a student spends in lessons, which equation can be used to find the value of h?
Answer:
The first one should be right. Since the teacher is charging $15 per hour of the piano lesson then it can't be any of the answers of $100h. The answer can't be C, the third one, since you're adding the enrollment fee to the cost of every piano lesson it would be wrong to subtract the $100. Hope that helps!
Step-by-step explanation:
The answer will the answer on the top $25=$100+$15h over h
Answer: The number of hours is 10 hours.
Step-by-step explanation:
Since we have given that
Average cost of lessons = $25
let h be the number of hours a student spends in lessons.
Since each student has fee of $100 plus $15 per hour.
So, According to question, it becomes,
[tex]25=\dfrac{100+15h}{h}\\\\25h=100+15h\\\\25h-15h=100\\\\10h=100\\\\h=\dfrac{100}{10}\\\\h=10[/tex]
Hence, the number of hours is 10 hours.
What is each power of i with its multiplicative inverse.
1. i
2. i ^2
3. i ^3
4. i ^4
Answer:
1) multiplicative inverse of i = -i
2) Multiplicative inverse of i^2 = -1
3) Multiplicative inverse of i^3 = i
4) Multiplicative inverse of i^4 = 1
Step-by-step explanation:
We have to find multiplicative inverse of each of the following.
1) i
The multiplicative inverse is 1/i
if i is in the denominator we find their conjugate
[tex]=1/i * i/i\\=i/i^2\\=We\,\, know\,\, that\,\, i^2 = -1\\=i/(-1)\\= -i[/tex]
So, multiplicative inverse of i = -i
2) i^2
The multiplicative inverse is 1/i^2
We know that i^2 = -1
1/-1 = -1
so, Multiplicative inverse of i^2 = -1
3) i^3
The multiplicative inverse is 1/i^3
We know that i^2 = -1
and i^3 = i.i^2
[tex]1/i^3\\=1/i.i^2 \\=1/i(-1)\\=-1/i * i/i\\=-i/i^2\\= -i/-1\\= i[/tex]
so, Multiplicative inverse of i^3 = i
4) i^4
The multiplicative inverse is 1/i^4
We know that i^2 = -1
and i^4 = i^2.i^2
[tex]=1/i^2.i^2\\=1/(-1)(-1)\\=1/1\\=1[/tex]
so, Multiplicative inverse of i^4 = 1
1. If x[tex]y^{2}[/tex] and xy are perfect squares, where x and y are positive integers, what is the smallest value of x + y?
Answer:
8
Step-by-step explanation:
xy^2 = k*k y^2 x = k * k so x has to be a perfect square.
xy is a perfect square which means that since x is a perfect square (see above) then y will have to be as well
There is nothing that prohibits x = 4 and y = 4 as being the answer where x = y.
I think the smallest possible value for x + y is 8.
This excludes any possibility of 1 or 0 in some combination, although I would look into 1.
120 is increased by d % and increased by 25% . What is the result ?
Please see attached image for complete answer and steps in detail.
Answer:
The result is 150 + 1.5d
Step-by-step explanation:
We want to translate the wordings into algebraic expression.
Firstly, we increase 120 by d%
d% = d/100
So increasing 120 by d % means;
120 + (d/100 * 120)
= 120 + 1.2d
Then increase this by 25%
= (120 + 1.2d) + 25/100(120 + 1.2d)
= 120 + 1.2d + (120+1.2d)/4
= 120 + 1.2d + 30 + 0.3d
= 120 + 30 + 1.2d + 0.3d
= 150 + 1.5d
rewrite square root of -49 -4 in complex number notation please help
Note that if [tex]i^2=-1[/tex] than [tex]i=\sqrt{-1}[/tex],
Also note that [tex]\sqrt{ab}=\sqrt{a}\sqrt{b}[/tex]
So we have,
[tex]\sqrt{-49}=\sqrt{-1}\sqrt{49}=\boxed{7i}[/tex]
and,
[tex]\sqrt{-4}=\sqrt{-1}\sqrt{4}=\boxed{2i}[/tex]
Hope this helps.
r3t40
what is an irrational number that is between 5.2 and 5.5.
Answer:
The irrational number could be √30
Step-by-step explanation:
An irrational number is a number which can not be written as a ratio between two numbers and it can not be written as a simple fraction. In simple words we can not write it in p/q form.
Find an irrational number that is between 5.2 and 5.5.
Mostly irrational numbers are square root numbers.
So square the both numbers.
(5.2)^2 (5.5)^2.
27.04 , 30.25
It means that the number is between 27.04 and 30.25
We will pick number 30
Square root 30
√30 = 5.48
The irrational number could be √30
It is 5.48 to the hundredth....
Write the slope-intercept form of the equation that passes through the point (4,-6) and is parallel to the line y = -3/4x - 5 y = -3/4x - 3 y = -3/4x + 3 y = 4/3x + 2/3 y = 4/3x - 34/3
Answer:
[tex]\large\boxed{y=-\dfrac{3}{4}x-3}[/tex]
Step-by-step explanation:
The slope-intercept form of an equation of a line:
y = mx + b
m - slope
b - y-intercept
Parallel lines have the same slope.
===========================================
We have the equation of the line: [tex]y=-\dfrac{3}{4}x-5[/tex]
The slope is [tex]m=-\dfrac{3}{4}[/tex].
Put the value of the slope and the coordinates of the point (4, -6) to an equation of a line:
[tex]-6=-\dfrac{3}{4}(4)+b[/tex]
[tex]-6=-3+b[/tex] add 3 to both sides
[tex]-3=b\to b=-3[/tex]
Finally:
[tex]y=-\dfrac{3}{4}x-3[/tex]
i need help with question 2. i think my answer is incorrect.
Answer:
395
You are 100% right! You go!
Step-by-step explanation:
We are given f(x)=5x^2-2x+8 and are asked to find the value of the function at x=9.
So replace x with (9):
f(9)=5(9)^2-2(9)+8
f(9)=5(81)-18+8 I did the exponent 9^2 and 2(9) in this step:
f(9)=405-18+8 I did 5(81) in this step
f(9)=405-10 I did -18+8 in this step
f(9)=395
the sum of 1/5 and twice a number is equal to 4/5 subtracted from three times the number. find the number.
Answer:
1
Step-by-step explanation:
Your equation may be written as follows:
[tex]\frac{1}{5} +2n=3n-\frac{4}{5}[/tex]
Start by multiplying both sides by 5 to clear your fractions.
[tex]\frac{1}{5} +2n=3n-\frac{4}{5} \\1+10n=15n-4[/tex]
Next, subtract 10n from both sides.
[tex]1+10n=15n-4\\1=5n-4[/tex]
Add 4 to both sides.
[tex]1=5n-4\\5=5n[/tex]
Divide both sides by 5 to solve for n.
[tex]5=5n\\1=n[/tex]
Final answer:
By setting up an equation 1/5 + 2x = 3x - 4/5 and solving for x, we find that the number is 1.
Explanation:
The problem involves finding a number when given a relationship involving fractions and that number. The relationship is: the sum of 1/5 and twice a number is equal to 4/5 subtracted from three times the number. To find the number, we set up an equation and solve for the variable, which represents the number.
Let's denote the number as x. Our equation can be written as:
1/5 + 2x = 3x - 4/5
We bring all the x terms on one side and the constants on the other to solve for x:
2x - 3x = -4/5 - 1/5
-x = -1
x = 1
the sum of four consecutive odd integers is -72. What is the value of the four intergers
Answer:
let the integers be x, x+2, x+4 and x+6
therefore,
x + x+2 + x+4 + x+6 = -72
=> 4x + 12 = -72
=> 4x = -72 - 12
=> x = -84/4
=> x = -21
therefore the integers are: -21, -19, -17, -15
[tex]\huge\boxed{\text{-21, -19, -17, -15}}[/tex]
Represent this mathematically. [tex]x+(x+2)+(x+4)+(x+6)=-72[/tex]
Combine like terms. [tex]4x+12=-72[/tex]
Subtract 12 from both sides. [tex]4x=-84[/tex]
Divide both sides by 4. [tex]x=-21[/tex]
Find the numbers by adding 2 each time. [tex]-21, -19, -17, -15[/tex]
10x^3 y^-5 z^-2 if x=3 y=2 and z=5 express your answer as a reduced fraction
Answer:
[tex]\large\boxed{\dfrac{27}{80}}[/tex]
Step-by-step explanation:
Put x = 3, y = 2 and z = 5 to the given expression [tex]10x^3y^{-5}z^{-2}[/tex]:
[tex]10(3^3)(2^{-5})(5^{-2})\qquad\text{use}\ a^{-n}=\dfrac{1}{a^n}\\\\=\dfrac{10(27)}{(2^5)(5^2)}=\dfrac{270}{(32)(25)}=\dfrac{270}{800}=\dfrac{27}{80}[/tex]
Linda is twice the age of Vera.
Tanya is four less than four times the age of Linda.
Their total age is two more than nine times the age of Vera.
How old is Tanya?
Answer:
Tanya is 20 years old
Step-by-step explanation:
Let the age of Vera = x years
The age of Linda is twice the age of Vera = 2x years
Tanya is four less than four times the age of Linda = 4(2x)-4 = 8x-4
Total age of Vera, Linda and Tanya is:
x+2x+8x-4
Combine the like terms:
11x-4
But now their total age is two more than nine times the age of Vera:
11x-4 = 9x+2
Solve the expression
Combine the like terms:
11x-9x=2+4
2x=6
Divide both the sides by 2
2x/2 = 6/2
x= 3
Thus the age of Vera is 3 years.
The age of Linda is 2x= 2*3 = 6 years
The age of Tanya is 8x-4 = 8*3 - 4 = 24-4 = 20years....
a^-3 over a^-2b^-5 write without rational notation and move all terms to numerator
Answer:
[tex]\large\boxed{\dfrac{a^{-3}}{a^{-2}b^{-5}}=a^{-1}b^5}[/tex]
Step-by-step explanation:
[tex]\dfrac{a^{-3}}{a^{-2}b^{-5}}=a^{-3}\cdot\dfrac{1}{a^{-2}}\cdot\dfrac{1}{b^{-5}}\qquad\text{use}\ x^{-n}=\dfrac{1}{x^n}\\\\=a^{-3}\cdot a^2\cdot b^5\qquad\text{use}\ x^n\cdot x^m=x^{n+m}\\\\=a^{-3+2}b^5=a^{-1}b^5[/tex]
If f(x) = 4 – x2 and g(x) = 6x, which expression is equivalent to (9 - 1)(3)?
Answer:
(g − f) ( 3 ) = 23
Step-by-step explanation:
( g − f ) ( x ) = g ( x ) − f ( x )
= 6 x − ( 4 − x 2 )
= x 2 + 6 x − 4
to evaluate ( g - f ) ( 3 ) substitute x = 3 into ( g − f ) ( x )
( g − f ) = ( 3 ) 2 + ( 6 x 3 ) - 4 =23
For this case we have the following functions:
[tex]f (x) = 4-x ^ 2\\g (x) = 6x[/tex]
By definition we have to:
[tex](f-g) (x) = f (x) -g (x)\\(g-f) (x) = g (x) -f (x)[/tex]
Then, we find [tex](f-g) (x):[/tex]
[tex]f (x) -g (x) = 4-x ^ 2-6x = -x ^ 2-6x 4[/tex]
We evaluate the function in 3:
[tex](f-g) (3) = - (3) ^ 2-6 (3) 4 = -9-18 4 = -27 4 = -23[/tex]
Now we find[tex](g-f) (x):[/tex]
[tex]g (x) -f (x) = 6x- (4-x ^ 2) = 6x-4 x ^ 2 = x ^ 2 6x-4[/tex]
We evaluate the function in 3
[tex](g-f) (3) = 3 ^ 2 6 (3) -4 = 9 18-4 = 23[/tex]
Answer:
[tex](f-g) (3) = - 23\\(g-f) (3) = 23[/tex]
Write the slope-intercept form of the equation that passes through the point (2, 3) and is perpendicular to the line y = 5/8x - 4
Answer:
[tex]\large\boxed{y=-\dfrac{8}{5}x+\dfrac{31}{5}}[/tex]
Step-by-step explanation:
[tex]\text{The slope-intercept form of an equation of a line:}\\\\y=mx+b\\\\m-slope\\b-y-intercept[/tex]
[tex]\text{Let}\\\\k:y=m_1x+b_1\\\\l:y=m_2x+b_2\\\\l\ \perp\ k\iff m_1m_2=-1\to m_2=-\dfrac{1}{m_1}\\\\l\ \parallel\ k\iff m_1=m_2\\\\--------------------------[/tex]
[tex]\text{We have:}\\\\y=\dfrac{5}{8}x-4\to m_1=\dfrac{5}{8}\\\\\text{The slope of a perpendicular line:}\ m_2=-\dfrac{1}{\frac{5}{8}}=-\dfrac{8}{5}\\\\\text{The equation:}\\\\y=-\dfrac{8}{5}x+b\\\\\text{Put the coordinates of the point (2, 3) to the equation:}\\\\3=-\dfrac{8}{5}(2)+b\qquad\text{solve for}\ b\\\\3=-\dfrac{16}{5}+b\qquad\text{add}\ \dfrac{16}{5}\ \text{to both sides}\\\\\dfrac{15}{5}+\dfrac{16}{5}=b\to b=\dfrac{31}{3}\\\\\text{Finally:}\\\\y=-\dfrac{8}{5}x+\dfrac{31}{5}[/tex]
factor the trinomial below. 4x^2+23-6. which two binomials are factors of the trinomial
Answer:
4x - 1 and x + 6 are the factors of given Trinomial
Step-by-step explanation:
The given Trinomial is:
[tex]4x^{2}+23x-6[/tex]
We can factorize this trinomial by mid-term splitting. The mid-term(23x) can be split up in two terms (24x and -x) such that their sum is 23x and their product(-24x²) is equal to the product of other two terms (4x² and -6)
So, the above expression can be written as:
[tex]4x^{2}+23x-6\\\\ =4x^{2}+24x-x-6\\\\\text{Taking out commons, we get}\\\\=4x(x+6)-1(x+6)\\\\ =(4x-1)(x+6)[/tex]
Therefore, 4x - 1 and x + 6 are the factors of given Trinomial
Answer: 4x-1 and x+6
Step-by-step explanation: a p e x
The perpendicular bisector of a chord...
Choices A and C are both true statements.
But C is trivial. It's CALLED a perpendicular "bisector" of the chord, so OF COURSE it bisects the chord ... otherwise it would be silly to CALL it a "bisector".
The choice that's surprising but true is A .
The perpendicular bisector of a chord passes through the center of the circle.
What is a chord?A chord in plane geometry is a line segment that connects two points on a curve. A line segment whose endpoints are on a circle is frequently described using this phrase. A cycle chord of a graph cycle is an edge that is not in and whose endpoints are in, according to graph theory, which also uses the phrase.
To know more about chords refer to :
https://brainly.com/question/4470346
#SPJ2
What was done to the quadratic parent function F(x) = x2 to get the
function G(x) = x2 - 3? 0)
A.Shifted 3 units to the right
B. Vertically stretched by multiplying by 3
C.Shifted 3 units down
D.Shifted 3 units to the left
ОА ОВ Oc OD
HINT
SUBMIT
Answer:
Option C.
Step-by-step explanation:
If k<0, the function g(x) = f(x) + k represents the function f(x) shifted k units downwards.
In this case, given that k=-3 (k<0). The graph was shifted 3 units down. Therefore, the correct option is Option C.
hat is the approximate area of the circle shown below?
A. 60 in 2
B. 119 in 2
c. 4536 in 2
d. 1134 in 2
Help Me Please!!!!!!!!!!!!!!!!!!!!!!
Answer:
d. 1134 inches squared
Step-by-step explanation:
The formula for the area of a circle is [tex]\pi r^2[/tex]
where r is the radius.
You are given r=19 here so replace r in [tex]\pi r^2[/tex] with 19 giving us:
[tex]\pi (19)^2[/tex]
Then it is to the calculator we go:
1134 inches squared
The length of a rectangle frame is represented by the expression 2x +8, and the width of the rectangle frame is represented by the expression 2x +6 what is the width of the rectangle frame that has a total area of 160 Square inches
Final answer:
The width of the rectangle frame with a total area of 160 square inches, and expressions for length (2x + 8) and width (2x + 6), is found to be 10 inches.
Explanation:
To solve for the width of the rectangle frame with an area of 160 square inches, where the length is represented by 2x + 8 and the width by 2x + 6, we need to set up an equation using the formula for the area of a rectangle, which is length × width. With the given area of 160 square inches, the equation is:
(2x + 8)(2x + 6) = 160
Let's expand this and solve for x:
4x² + 12x + 16x + 48 = 160
4x² + 28x + 48 = 160
4x² + 28x - 112 = 0
Divide everything by 4 to simplify:
x²+ 7x - 28 = 0
Factor this quadratic equation:
(x + 14)(x - 2) = 0
x = -14 or x = 2
Since a width cannot be negative, x = 2
Now, to find the width, replace x in the width expression:
Width = 2x + 6
Width = 2(2) + 6 = 4 + 6 = 10 inches
Thus, the width of the rectangle frame is 10 inches.
which value is equivalent to (7x5x2/7x3)^2 x (5^0/2^-3)^3 x2^-9?
Answer:
100/9
Step-by-step explanation:
(7*5*2/7*3)² * (5^0/2^-3)³ * 2^-9
Solution:
We know that any number with power 0 = 1
(7*5*2/7*3)² * (1/2^-3)³ * 2^-9
Now cancel out 2 by 2
= (7*5*2/7*3)² * (1/1^-3)³ * 1^-9
=(70/21)² * (1)³/(1^-3)³ * 1^-9
=(10/3)^2 * 1/1^-1 * 1/1^9
=100/9 *1 *1
=100/9....
simplify -(x+5) + 3x completely
Answer:2x-5
Step-by-step explanation:-(x+5)+3x
-x-5+3x=(3x-x) -5
=2x-5
In the Pythagorean Theorem, what
does the "a" stand for?
a2 + b2 = c2
A. The longest side, or hypotenuse, of a right triangle.
B. One of the sides, or legs, that make up the right
angle.
C. Any unknown side of a right triangle.
Answer:
B. One of the sides, or legs, that make up the right angle.
Step-by-step explanation:
The Pythagoras Theorem applies to the right-angled triangles. It is basically a relationship between the sizes of the all lengths of the triangle. The Pythagoras Theorem is given by:
C^2 = A^2 + B^2; where A and B are perpendicular and base respectively, and C is the hypotenuse. It is interesting to note that A can either be the perpendicular or the base of the right angled triangle. Same goes for B; it can be either the perpendicular or the base. Both the perpendicular and the base intersect at 90 degrees. But both cannot be the hypotenuse. Therefore, the variable A in the Pythagoras Theorem is one of the sides, or legs, that make up the right angle, i.e. Option B is the correct answer!!!
Find the missing value in the pair of similar polygons.
Convert -sqrt3 - i to polar form. PLEASE HELP. Photo has more information
Answer:
-√3 - i ⇒ (2 , 7/6 π)
Step-by-step explanation:
* Lets explain how to convert a point in Cartesian form to polar form
- Polar coordinates of a point is (r , θ).
- The origin is called the pole, and the x axis is called the polar axis,
because every angle is dependent on it.
- The angle measurement θ can be expressed in radians or degrees.
- To convert from Cartesian Coordinates (x , y) to Polar
Coordinates (r , θ)
1. r = √( x² + y² )
2. θ = tan^-1 (y/x)
* Lets solve the problem
∵ The point in the Cartesian form is z = -√3 - i, where -√3 is the real
part and -i is the imaginary part
∴ The x-coordinate of the point is -√3
∴ The y-coordinate of the point is -1
∵ Both the coordinates are negative
∴ The point lies on the 3rd quadrant
- To convert it to the polar form find r and Ф
∵ [tex]r=\sqrt{x^{2}+y^{2}}[/tex]
∵ x = -√3 and y = -1
∴ [tex]r=\sqrt{(-\sqrt{3}) ^{2}+(-1)^{2}}=\sqrt{3+1}=\sqrt{4}=2[/tex]
∵ Ф = [tex]tan^{-1}\frac{y}{x}[/tex]
∴ Ф = [tex]\frac{-1}{-\sqrt{3}}=\frac{1}{\sqrt{3}}[/tex]
- The acute angle π/6 has tan^-1 (1/√3)
∵ The point is in the third quadrant
∴ Ф = π + π/6 = 7/6 π
- Lets write it in the polar form
∴ -√3 - i ⇒ (2 , 7/6 π)
Answer:
2cis 7pi/6
Step-by-step explanation:
Classify the following triangle. Check all that apply.
Answer:
obtuse, isosceles
Step-by-step explanation:
We have two angles that have the same measure - that means two sides are equal length. That means the triangle is isosceles
We have one angle that is greater than 90 degrees - that tells us the triangle is obtuse
I need help with #17 please and thank you!
Which one of the following is equal to 1hector area? 10000m/square 10000m/square 100m/square
100000m/square
Answer:
10,000 m/square
Step-by-step explanation:
we know that
A hectare is a unit of area equal to [tex]10,000\ m^{2}[/tex]
The symbol is Ha
Verify each case
case 1) 10,000 m/square
The option is true
case 2) 100 m/square
The option is false
case 3) 100,000 m/square
The option is false
x³-64 in prime factored form
[tex]\bf \textit{difference and sum of cubes} \\\\ a^3+b^3 = (a+b)(a^2-ab+b^2) \qquad \qquad a^3-b^3 = (a-b)(a^2+ab+b^2) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ x^3-64\implies x^3-4^3\implies (x-4)(x^2+4x+4^2)\implies (x-4)(x^2+4x+16)[/tex]
Amanda owns a clothing store that sells graphic t-shirts. n is the number of shirts she sells each month. the revenue function of her store is r = 15n. the cost function of her store is c = 9n + 450. using your calculator, what is the break-even point of amanda's store?
Answer:
The break- even point is attained when n=75
Step-by-step explanation:
The break-even point is defined as the point where revenue is equal to cost.
We take the equation for revenue r=15n, and set it equal to the equation c=9n+450
15n=9n+450
Subtract 9n from both sides:
6n=450
Divide both sides by 6.
6n/6=450/6
n=75
The break- even point is attained when n=75....
Final answer:
To determine Amanda's store's break-even point, set the revenue equal to the cost function and solve for n to find 75 shirts.
Explanation:
To find the break-even point of Amanda's store:
Set the revenue function equal to the cost function: 15n = 9n + 450
Solve for n: n = 75
Therefore, the break-even point is when Amanda sells 75 graphic t-shirts.